RavenClaw: Dialog Management Using Hierarchical Task Decomposition and an Expectation Agenda - Bohus, Dan; Rudnicky, Alexander I. (Eurospeech 2003-Switzerland - 8th European conference on speech communication and technology, 2003)
We describe RavenClaw, a new dialog management framework developed as a successor to the Agenda architecture used in the CMU Communicator. RavenClaw introduces a clear separation between task and discourse behavior specification, and allows rapid development of dialog management components for spoken dialog systems operating in complex, goal-oriented domains. The system development effort is focused entirely on the specification of the dialog task, while a rich set of domain-independent conversational behaviors are transparently generated by the dialog engine. To date, RavenClaw has been applied to five different domains allowing us to draw some preliminary conclusions as to the generality of the approach. We briefly describe our experience in developing these systems.